Digital Banking Research Trends: A Bibliometric Analysis of Banking Technology Developments - Farichah, Miftahul; Lamondo, Mohamad Safriyanto (Faculty of Islamic Economics and Business, Madura Islamic State University, 2025)
This research aims to analyze the trend of digital banking research on the development of banking technology through a bibliometric approach. The method used in this study uses a mixed-method, which is a combination of quantitative methods in the form of a bibliometric analysis approach and qualitative methods in the form of a literature review study. The data in this study were obtained from secondary data. Data analysis tools use Mendeley Desktop and VOSviewer software. The analysis was conducted on abstracts and research keywords related to the development of digital banking-based banking technology. The results of the study show that; 1) based on the mapping of journal publications, there are 76 articles on the development of digital banking technology; 2) the results of network visualization around the development of digital banking technology are divided into 6 clusters and 25 topic items; 3) there are four problems that are challenges in the development of banking technology, 1) cybersecurity, 2) digital financial literacy, 3) infrastructure gaps, and 4) regulation and compliance.